THE RELATIONSHIP BETWEEN PARENTING STYLES AND ACADEMIC SELF-ESTEEM AMONG PRESCHOOL CHILDREN IN SABANG - Salmiati (Jurnal Buah Hati, 2015)
Parenting styles play an important role in child development. Extensive studies have been conducted concerning on the relationship between parenting styles and adolescents’ self-esteem. However, the studies focusing on the relationship between parenting styles and preschool children’s academic self-esteem are highly limited. Hence, this study observed the relationship between parenting styles and self-esteem among preschool children’s in Sabang. A total of 107 preschool children’s parents completed the Parenting Style Dimensional Questionnaires (PSDQ) and their children were observed by teachers using Behavioral Academic Self-Esteem (BASE). The result showed that authoritative parenting style was predominantly practiced by parents and most children displayed moderate academic self-esteem. A significant relationship was found between authoritarian and academic self-esteem (r = -.461, p < .05). In addition, a significant correlation was also found between authoritative parenting style and academic self-esteem (r .348, p < .05), while there was no significant relationship between permissive parenting style and academic self-esteem (r = .000, p > .000). The findings indicated that there were no differences in academic self-esteem among male students (M= 1.85, SD= .583, n = 48) and female students (M= 2.10, SD= .51, n = 59) and t (-. 2300 (95) p < .05. The implications and suggestions will also be discussed in the light of finding.